The mediating role of the strength of compromise between the identity processing styles and well-being of emerging young adults - Sánchez-Queija, Inmaculada; Pineda-Balbuena, Ángela; Díez, Marta; Parra, Águeda (Anales de Psicología / Annals of Psychology, 2023)
Background: Identity styles seek to know how people handle themselves daily in situations looking for an identity commitment. This article aims to find out whether identity styles vary according to age and sex, and to analyze the relation between these identity styles and the strength of commitment with variables of well-being and psychological distress. In addition, it investigates whether commitment mediates between identity styles, well-being and psychological distress. Method: 278 participants (M = 22.03; DT = 2.65), recruited through a non-probabilistic snowball sampling, completed the questionnaires. Results: Women scored higher in strength of commitment and men adopted a more diffusive-avoidant style. Age did not relate to identity style. The informational style correlated positively with well-being variables (flourishing and optimism); the normative style with depression and anxiety and the diffuse-avoidant style correlated positively with psychological distress (depression, anxiety and stress) and negatively with well-being. Finally, the greater the strength of commitment found, the more flourishing and optimism and the less psychological distress there was. The strength of commitment partially or totally mediated the relationship between identity styles and the variables of well-being / psychological distress. Conclusions: The importance of the strength of commitment in personal well-being and the necessity to favour the development of young people´s identity is observed / deduced.